An open randomized study to compare effect of metformin versus acarbose monotherapy on glycemic control and lipid profile in newly diagnosed type 2 diabetes mellitus patients - Manda, Ram A.; Verma, Veena; Biswas, Krishna (International Journal of Research in Medical Sciences, 2021)
Background: Type 2 DM is one global health problem and a main cause of morbidity and mortality. It is epidemic in many industrialized and developing areas and is considered to be one of the most challenging health problems of the 21st century. Metformin and acarbose both are used as monotherapy and in combination with other anti-diabetes drugs for treatment of type 2 DM. There are very sparse evidences regarding comparative efficacy and safety of metformin versus acarbose, especially in Asian region. In addition to glycemic control, improvement in lipid profile, weight loss and post-prandial sugar level are important therapeutic objectives for better management of type 2 DM patients. Methods: In this study, 60 newly diagnosed type 2 DM were randomly assigned (1:1) to oral acarbose (titrated doses upto 300 mg daily) or oral metformin (titrated doses up to 2500 mg daily) monotherapy and were followed-up for 12 weeks for effects on glycaemic control [serum HbA1C, fasting blood sugar and post prandial sugar and serum LDL, HDL, triglycerides and total cholesterol. Results: Reduction in FBS, HbA1C and body weight was found significantly greater with metformin while acarbose yielded greater improvement in PPS, total cholesterol and triglyceride levels. Both metformin and acarbose yielded significant improvement in FBS, PPS, HbA1C, lipid profile and body weight after 12 weeks of therapy and yielded similar improvement in LDL and HDL levels. Conclusions: Acarbose can be considered as an alternative initial therapy in newly diagnosed type 2 diabetes patients, particularly those with isolated post-prandial hyperglycemia and those who are intolerant to metformin therapy.